THE ROLE OF INNOVATION IN IMPROVING PUBLIC ADMINISTRATION EFFICIENCY - Herijanto Bekti (Sean Institute, 2022)
The complex challenges faced by public administration, such as the increasing complexity of societal demands, the need to maintain and improve performance, and limited resources, require innovative approaches to achieve optimal efficiency. This study aims to examine the role of innovation in increasing the efficiency of public administration. Public administration is an important component in running an effective government and providing quality services to the public. This study uses a descriptive analysis method involving literature studies and qualitative analysis. The research results show that innovation has an important role in increasing the efficiency of public administration. Innovations in public administration can include the application of information technology, development of more effective management systems, changes to policies and procedures that are more responsive, and human resource capacity building. In a broader context, innovation also involves collaboration between government, the private sector, and communities in designing innovative solutions to complex public administration problems. Through innovation, the efficiency of public administration can be increased through the use of better technology, efficient data management, and improving the quality of public services . Innovation can also speed up the decision-making process, increase transparency and accountability, and strengthen the relationship between government and society.